Seis meses de aleitamento materno exclusivo no pré-termo de muito baixo peso submetido ao método canguru - Kallyne Estevão Fernandes Santos; Julianne Christine Gadelha Vilela; Thaíssa Paschôa Costa; Élida Falcão de Castro; Claudia Rodrigues Souza Maia (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To know the rate and factors associated with exclusive breastfeeding in the follow-up of the preterm submitted to the kangaroo method. METHODS: Cross-sectional study performed with pre-terms smaller than 33 weeks and/or birth weight <1,500 grams, born in 2019, submitted to the kangaroo method and followed up to six months. Descriptive analysis and association and comparison tests were carried out for the maternal and neonatal factors for the outcome of exclusive breastfeeding yes (G1) and not (G2) by the IBM-SPSS/Statistics program 22. RESULTS: Of the 111 patients who were discharged, 82 (100%) were followed up to the corrected ages 3.8/4.2 and chronological 5.9/6.3 months, respectively, in the G1/G2. Exclusive breastfeeding was present in G1 at 22 (26.8%) patients and 60 (73.2%) in the G2 had already introduced formula. Maternal age averages 28/29 years, gestational age 30.3/30.4 weeks, birth weight 1295/1434g, mechanical ventilation time 5.0/5.8 and total hospitalization 56/49 days in groups G1 and G2, respectively. Cesarian section frequencies 68/61%, necrotizing enterocolitis 4.5/8.3%, severe peri-intraventricular hemorrhage 4,5/8.3%, late sepsis 19/16.9%, and rehospitalization after discharge 4.5/6,8% in G1 and G2 patients. There was no statistical significance of the variables analyzed for the outcome of exclusive breastfeeding. CONCLUSION: Compared to other cohorts and at the service itself in 2010 analysis, the breastfeeding rate was high and, especially the exclusive breastfeeding, condition associated with the best development of the preterm. The perinatal variables were not determinants of the success of exclusive breastfeeding in these patients treated by the kangaroo method.